Amygdala and oxytocin functioning as keys to understanding and treating autism: Commentary on an RDoC based approach. (November 2018) - Preckel, Katrin; Kanske, Philipp
Abstract: The recent review by Hennessey, Andari and Rainnie (2018) utilizes the proposed Research Domain Criteria (RDoC) to classify amygdala functions and relate them to autism symptomatology. This approach has the potential to challenge the overarching autism diagnosis by furthering our knowledge of the mechanisms giving rise to autism psychopathology and generate novel treatment options. The purpose of this commentary is to provide additional information on a number of points raised in the review. Thus, (1) we discuss the issue of amygdala and brain overgrowth in children with autism and relate it to developmental oxytocin changes, (2) examine potential mechanisms that underlie amygdala overgrowth and dysfunction of the oxytocin system, (3) zoom in on the sexually dimorphic characteristics of the amygdala and potential parallels with the oxytocin system and (4) discuss how the interplay of oxytocin and vasopressin may explain the partially inconsistent findings of their effects on amygdala functioning.